Efficiency of State Universities and Colleges in the Philippines: a Data Envelopment Analysis - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2011)
In view of the long-standing issues and concerns that beset the Philippine system of higher education, the study attempts to evaluate the performance of state universities and colleges (SUCs) in the period 2006-2009 using Data Envelopment Analysis (DEA). In particular, it estimates the efficiency of 78 SUCs based on available input data (i.e., expenditure data) and output data (i.e., number of enrolled students, number of graduates, and total revenue). Also, it examines productivity change in these institutions by applying the Malmquist approach on a four-year panel data set of 78 SUCs. The DEA results indicate that majority of the SUCs have efficiency score less than 1 and thus, they are considered inefficient. In addition, the target input and output levels derived from the DEA suggest potential cost savings for each of the SUCs. Further, productivity of about 62 percent of the SUCs has slightly improved in the period under review. The findings of the study point to a potential research in the future that would take a closer look on each of the SUCs identified as inefficient in this exercise with the end in view of identifying, understanding, and hopefully, addressing the factors that affect their operation and performance.
Keywords: 330; productivity; efficiency; higher education; Philippines; higher education institutions (HEIs); Revitalized General Education Program (RGEP); gambling; state universities and colleges (SUCs); data envelopment analysis; Hochschule; Effizienz; Data-Envelopment-Analyse; Philippinen